New Isoflavonoids from the extract of Rhynchosia precatoria (Humb. & Bonpl. ex Willd.) DC. and their antimycobacterial activity. (12th July 2017) - Coronado-Aceves, Enrique Wenceslao; Gigliarelli, Giulia; Garibay-Escobar, Adriana; Zepeda, Ramón Enrique Robles; Curini, Massimo; López Cervantes, Jaime; Inés Espitia-Pinzón, Clara Inés; Superchi, Stefano; Vergura, Stefania; Marcotullio, Maria Carla
Abstract: Ethnopharmacology relevance: The evaluation of the antimycobacterial activity of extracts of medicinal plants used by Mayos against tuberculosis and respiratory problems, allowed the identification of Rhynchosia precatoria (Humb. & Bonpl. ex Willd.) DC (Fabaceae) as the best candidate to find new antimycobacterial compounds. Aim of the study: To isolate and characterize the compounds of R. precatoria responsible for the inhibitory and bactericidal activity against Mycobacterium tuberculosis H37Rv and Mycobacterium smegmatis ATCC 700084. To determine antimycobacterial synergistic effect of pure compounds and their selectivity index towards Vero cells. Materials and methods: A total of six flavonoids were purified by silica gel column chromatography. Structural elucidation of the isolated compounds was achieved by using 1D and 2D NMR spectroscopy techniques. The configuration at the C-3 chiral center was established by quantum mechanical calculation of the electronic circular dichroism (ECD) spectrum. In vitro inhibitory and bactericidal activity against M. tuberculosis and M. smegmatis were determined with the redox indicator Alamar Blue (resazurin). Synergy was determined by X/Y quotient. Cytotoxicity was measured by MTT assay. Results: The isolated compounds were identified as precatorin A (1 ), precatorin B (2 ), precatorin C (3 ), lupinifolin (4 ), cajanone (5 ) and lupinifolinol (6 ). Compounds1 –3 are new. Compounds1 to5 inhibited the growth of M. tuberculosis (MIC ≥31.25 µg/mL); compounds1, 2, 4 and5 killed the bacteria (MBC ≥31.25 µg/mL) and also inhibited M. smegmatis (MIC ≥125 µg/mL), while1 and4 also resulted bactericidal (MBC ≥125 µg/mL). Compounds4 and5 presented synergistic effect (X/Y quotient value <0.5) at a concentration of 1/2 MIC of each compound in the combination. Cytotoxicity in murine macrophages (RAW 264.7 cells) gave IC50 values of 13.3–46.98 µM, for compounds1 –5 . Conclusions: In this work we isolated two new isoflavanones (1 and2 ), and one new isoflavone (3 ) with a weak antimycobacterial activity. The (3 R ) absolute configuration was assigned to1 by computational analysis of its ECD spectrum and to2 and5 by similarity of their ECD spectra with that of1 . We are also reporting by first time, activity against virulent strain of M. tuberculosis for compounds4 and5 and their antimycobacterial synergistic effect. Graphical abstract: